PROSEDUR PENELITIAN KUANTITATIF - Murjani Murjani (Cross-border, 2022)
Research methods with a quantitative approach are often referred to as traditional methods, because this method has been used for a long time so that it has become a tradition as a method for research. In addition, this method is also referred to as the positivistic method, because it is based on the philosophy of positivism. In quantitative research between objectives, hypotheses, methods are interrelated. Where one character determines the other.